First report on severe septic shock associated with human Parvovirus B19 infection after cardiac surgery - Xiang, Chunlin; Wu, Xiaoxiao; Wei, Youkang; Li, Tianlong; Tang, Xuemei; Wang, Yi; Zhang, Xiaoqin; Huang, Xiaobo; Wang, Yiping (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Background: Human Parvovirus B19 (PB19) is a single-stranded DNA virus. Septic shock from viremia is rare with PB19; however, this infection can progress to life-threatening conditions. We report the first case of severe septic shock associated with a PB19 infection after cardiac surgery. Case Presentation: A 50-year-old Chinese woman received elective double metal valve replacement, including the aortic valve and the mitral valve, under cardiopulmonary bypass (CPB) and suffered severe septic shock on postoperative day (PD) 30. Through the detection of PB19-specific nucleic acids in blister fluid and serum samples via metagenomic next-generation sequencing (mNGS), positive serum PB19 IgM and no other proven infection, acute PB19 infection was confirmed. After five days of combined treatment, no further fever or abdominal discomfort was noted, and the patient’s circulation gradually became stable without vasoactive medications. Conclusion: PB19 may be an unrecognized cause of septic shock, rash, fever of unknown origin or multiple systemic signs and symptoms, especially in immunosuppressed and immunocompetent critically ill patients. Investigations for viral aetiology are needed.